Fungsi serta Kegunaan Microsoft Publisher bagi Dunia Kerja - Nina Amanda; Ayu Syahputri; Diki Ariansyah Putra; Luthfi Lisikmiko; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
This article deals with the impact of the benefits of Microsoft Publisher in the world of work. Using Microsoft Publisher, you can practically produce a publication because it has provided a large selection of publication templates that can be used. In addition, you can also create your own design on a blank page (blank page size) by selecting the type of publication available. Microsoft Publisher program is now widely used in the world of printing and advertising to create various kinds of publications such as brochures, pamphlets, business cards, calendars, posters, banners, book designs, information letters and others. The results of the study show that the advantages of the Microsoft Publisher program are that it is practical in managing the placement of text and images, many choices of publication types, ranging from certificate ads, banners, brochures, business cards, business forms, calendars, catalogs, and so on. In addition, you can design web pages (web design) and publish them to the internet